Predicting Spatial Distribution of Argilic Horizon Using Auxilary Information in Regional Scale - Yiyi Sulaeman; D Djaenudin (Jurnal Ilmu Tanah dan Lingkungan, 2005)
For supporting better soil management, the spatial distribution of soils having argilic hori=on (argilic soils) must berecognized and it can be delineate in soil survey mapping activity, but this activity consumes much time and money. This study aimed to build a decision tree model for predicting the spatial distribution of argillic hori=on based on auxiliary information using 3 predicting environmental variables; namely, geomorphic sUrface or substrate, landsurjace unit, and ecoregion beh.Three-based modeling technique was used to generate classification tree model from 318 pedon of Lampung Province,Indonesia. Argillic horizon is predicted to present in hot belt (elevation of 0-200 m above sea level) on interfluve-seepageslope with probability 84% for acid igneous rock, 83% for basic igneous rock, and 90% for acid sedimentary rock. Argillichorizon is also predicted to present in hot belt on transportational midslope with the probability 65% for transported acid sedimentary rock. Argillic horizon is predicted absent with the probability to occur ranging from 0% to 32% on otlrer combinations of landsurface unit, ecoregion belt, and substrate.